Efficacy of interval exercise training to improve vascular health in sedentary postmenopausal females. Issue 16 (19th August 2022) - Lyall, Gemma K.; Birk, Gurpreet K.; Harris, Emma; Ferguson, Carrie; Riches‐Suman, Kirsten; Kearney, Mark T.; Porter, Karen E.; Birch, Karen M.
Abstract: Background: Menopause represents a turning point where vascular damage begins to outweigh reparative processes, leading to increased cardiovascular disease (CVD) risk. Exercise training reduces CVD risk in postmenopausal females via improvements in traditional risk factors and direct changes to the vasculature. We assessed the effect of moderate (MODERATE‐IT) versus heavy (HEAVY‐IT) intensity interval exercise training upon markers of cardiovascular health and vascular repair in postmenopausal females. Methods: Twenty‐seven healthy postmenopausal females (56 ± 4 yr) were assigned to 12 weeks of either MODERATE‐IT or HEAVY‐IT, twice per week. MODERATE‐IT consisted of 10s work, and 10s active recovery repeated for 30 min. HEAVY‐IT comprised 30s work, and 30s active recovery repeated for 21 ± 2 min. Endothelial function (flow‐mediated dilation), arterial stiffness (pulse wave velocity), and V̇O2peak were assessed pre‐training and post‐training. Blood samples were obtained pre‐training and post‐training for enumeration of circulating angiogenic cells (CACs), culture of CACs, and lipoprotein profile. Results: V̇O2peak increased 2.4 ± 2.8 ml/kg/min following HEAVY‐IT only ( p < 0.05). Brachial blood pressure and endothelial function were unchanged with exercise training ( p > 0.05). Peripheral pulse wave velocity reduced 8% with exercise training, irrespective of intensity ( p < 0.05). Exercise training had no effect on lipoprotein profile or endothelin‐1 ( p > 0.05). CAC adhesion to vascular smooth muscle cells (VSMC) increased 30 min post plating following MODERATE‐IT only ( p < 0.05). Conclusions: HEAVY‐IT was more effective at increasing V̇O2peak in postmenopausal females. The ability of CACs to adhere to VSMC improved following MODERATE‐IT but not HEAVY‐IT. Interval training had the same effect on endothelial function (no change) and arterial stiffness (reduced), regardless of exercise intensity.